(untitled) (Confluenţe Bibliologice, 2017)
The qualitative assessment of the results of scientific research through IT indicators and tools is a very current and debatable issue in the academic environment. The research presents the analysis of webometric indicators and Webometrics ranking methodology, especially the Ranking Web of Repositories, from the perspective of the further development of IR SUMPh taking into account world best practices. There are some recommendations on the development of IR in order to participate in this ranking.